Where Immigrants Settle in the United States - Barry R. Chiswick; Paul W. Miller (Institute for the Study of Labor (IZA), 2004)
This paper is concerned with the location of immigrants in the United States, as reported in the 1990 Census. Where they settle has implications for the economic, social and political impact of immigrants. Immigrants are highly geographically concentrated. Compared to the native born they are more likely to live in the central parts of Metropolitan Areas in ?gateway (major international airport) cities? in six states (California, New York, Texas, Florida, New Jersey and Illinois). The shift away from the east coast metropolitan areas to California reflects the change in the origins of immigrants from Europe/Canada to Asia, Mexico and other parts of Latin America. Differences by linguistic origin and period of arrival are also considered.
Keywords: J15; R21; J61; 330; immigrants; residential location; language; Migranten; Wohnstandort; Stadtsoziologie; Regionale Konzentration; Schätzung; Vereinigte Staaten